Alleviating Oxidative Injury of Myocardial Infarction by a Fibrous Polyurethane Patch with Condensed ROS‐Scavenging Backbone Units. Issue 4 (2nd December 2021) - Xie, Jieqi; Yao, Yuejun; Wang, Shuqin; Fan, Linge; Ding, Jie; Gao, Yun; Li, Shifen; Shen, Liyin; Zhu, Yang; Gao, Changyou
Abstract: Excessive reactive oxygen species (ROS) generated after myocardial infarction (MI) result in the oxidative injury in myocardium. Implantation of antioxidant biomaterials, without the use of any type of drugs, is very appealing for clinical translation, leading to the great demand of novel biomaterials with high efficiency of ROS elimination. In this study, a segmented polyurethane (PFTU) with a high density of ROS‐scavenging backbone units is synthesized by the reaction of poly(thioketal) dithiol (PTK) and poly(propylene fumarate) diol (PPF) (soft segments), thioketal diamine (chain extender), and 1, 6‐hexamethylene diisocyanate (HDI). Its chemical structure is verified by gel permeation chromatography (GPC), 1 H nuclear magnetic resonance ( 1 H NMR) spectroscopy, and Fourier transform infrared (FTIR) spectroscopy. The electrospun composite PFTU/gelatin (PFTU/Gt) fibrous patches show good antioxidation capacity and ROS‐responsive degradation in vitro. Implantation of the PFTU/gelatin patches on the heart tissue surface in MI rats consistently decreases the ROS level, membrane peroxidation, and cell apoptosis at the earlier stage, which are not observed in the non‐ROS‐responsive polyurethane patch. Inflammation and fibrosis are also reduced in the PFTU/gelatin‐treated hearts, resulting in the reduced left ventricular remodeling and better cardiac functions postimplantation for 28 d. Abstract : The polyurethane (PFTU) with condensed reactive oxygen species (ROS)‐scavenging backbone units is used to fabricate the composite fibrous cardiac patch PFTU/gelatin, which exhibits excellent antioxidant activity, ROS‐responsive degradability, and presents better effect in reducing oxidative injury, cell apoptosis, inflammation, and improving cardiac functions when treating myocardial infarction in vivo.